(untitled) (Global Journal of Science Frontier Research, 2019)
Proportion of altitudes and temperatures of tropopause, stratopause and mesopause in the Earth’s atmosphere is estimated. A clear numerical coincidence is expressed in proportions of altitudes and temperatures of isothermal layers of Titan’s atmosphere. A statistically significant simultaneous proportion of altitudes and temperatures of isothermal layers was established in the atmosphere of Jupiter. Proportion values of temperatures and altitudes of isothermal layers is equivalent to the golden ratio constant, of the irrational number 1.6180339. Results in this paper indicate the possible function of the golden ratio constant in numerical models of the atmosphere.